Detection of filamentous fungi in foods. (October 2015) - Rodríguez, Alicia; Rodríguez, Mar; Andrade, María J; Córdoba, Juan J
Highlights: Accurate methods relying on genes involved in mycotoxin biosynthesis are available. qPCR allows sensitive detection/quantification of mycotoxins-producing fungi in foods. Molecular methods to detect spoilage filamentous fungi are based on constitutive genes. Limitations of molecular detection of filamentous fungi due to false results must be controlled. Abstract : Filamentous fungi (ff) are a constraint on food security. For detecting ff, culturing methods together with mycotoxin production evaluation or proteomic approaches are used but time and cost of analysis are too high. Genomic methods, such as PCR-based techniques and loop-mediated isothermal amplification, have been reported as rapid and accurate alternatives. Limitations of genomic methods due to false results must be controlled using internal amplification control and avoiding experimental conditions which favour mutant formation. To detect spoilage ff efficient methods such as MALDI-TOF MS, fluorescent staining, Fourier transform infrared spectroscopy analysis, hyperspectral imaging analysis and nucleic acid molecular methods with primers designed from single-copy or multi-copy genes, are proposed. Thus, rapid methods are available for an early and accurate detection of ff in foods.